2013
DOI: 10.2174/09298673113209990136
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic PPARs: Their Role in Liver Physiology, Fibrosis and Treatment

Abstract: Abstr act: Complex molecular and cellular mechanisms are involved in the pathway of liver fibrosis. Activation and transformation of hepatic stellate cells (HSCs) are considered the two main reasons for the cause and development of liver fibrosis. The peroxisome proliferator-activated receptors (PPARs) belonging to the family of ligand-activated transcription factors play a key role in liver homeostasis, regulating adipogenesis and inhibiting fibrogenesis in HSCs. Normal transcriptional function of PPARs contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 284 publications
(364 reference statements)
3
54
0
Order By: Relevance
“…We compared the F and S groups and observed that 166 genes were up-regulated and 244 genes were down-regulated. KEGG pathway analyses of the 410 differentially expressed genes indicated that many of the genes were enriched in the peroxisome proliferator-activated receptor (PPAR) signaling pathway, which is involved in lipid metabolism (Zardi et al, 2013) (Table 2). Genes involved in fatty acid oxidation (i.e., Glpk, Ubc, Cpt1, and Pgar) were up-regulated in the F group compared with the S group.…”
Section: Differential Gene Expression In the Two Groupsmentioning
confidence: 99%
“…We compared the F and S groups and observed that 166 genes were up-regulated and 244 genes were down-regulated. KEGG pathway analyses of the 410 differentially expressed genes indicated that many of the genes were enriched in the peroxisome proliferator-activated receptor (PPAR) signaling pathway, which is involved in lipid metabolism (Zardi et al, 2013) (Table 2). Genes involved in fatty acid oxidation (i.e., Glpk, Ubc, Cpt1, and Pgar) were up-regulated in the F group compared with the S group.…”
Section: Differential Gene Expression In the Two Groupsmentioning
confidence: 99%
“…Apart from de novo expression of α-SMA, reduced PPAR-γ expression is also a marker for HSC activation (20,21). The results of the present study showed that POP inhibitor significantly decreased, while lentivirus-mediated overexpression of POP increased the expression of PPAR-γ.…”
Section: Discussionmentioning
confidence: 46%
“…Peroxisome proliferator activated receptor-γ (PPAR-γ) was initially identified as a key regulator of adipogenesis (19), while increasing evidence has confirmed that PPAR-γ is a key factor in HSC activation and phenotypic alteration, maintaining HSCs in a quiescent phase, and suppressing the production of type I collagen, α-SMA and TGF-β1. Thus, PPAR-γ has an important role in reducing and preventing liver fibrosis (20,21). PPAR-γ can disrupt the TGF-β signaling pathway and Smad-dependent promoter activity, directly antagonizes the activation and/or function of Smad3 in fibroblasts without affecting the protein expression of stimulatory Smad3.…”
Section: Introductionmentioning
confidence: 99%
“…Pparg regulates adipogenesis, lipid metabolism and insulin sensitivity [22,23]. Pparg presents two promoter regions [24].…”
Section: Discussionmentioning
confidence: 99%
“…PPARs are ligand-dependent transcription factors that regulate target gene expression by binding to a PPAR at regulatory sites [22,23]. The PPAR gamma gene Pparg presents splicing variants with two protein isoforms (PPARG1 and PPARG2) and two promoter regions [24,25].…”
Section: Introductionmentioning
confidence: 99%